Programma: 15 december: Houdini's, Kickin' in the Frontwindow, Jazzdance D.J.'s Dr. Soul & Tin Tin, Jazzdancers A.D. & John (1993)
Programma: 15 december: Houdini's, Kickin' in the Frontwindow, Jazzdance D.J.'s Dr. Soul & Tin Tin, Jazzdancers A.D. & John.